Bistriopelma, a new genus with two new species from Peru (Araneae: Theraphosidae: Theraphosinae) - Kaderka, Radan (2015)
Bistriopelma gen. nov. from the Andean region in Peru is here described, diagnosed and illustrated, together with two new species Bistriopelma lamasi sp. nov. as a type species and Bistriopelma matuskai sp. nov. This new genus differs from all other theraphosid genera, except the genus Phrixotrichus Simon 1889 (sensu Perafán & Pérez-Miles 2014) and the troglobite species Tmesiphantes hypogeus Bertani, Bichuette & Pedroso 2013, in the presence of two abdominal dorsolateral patches of the type III urticating setae. Bistriopelma gen nov. can be distiguished from Phrixotrichus by the different shape of spermathecae in females, consisting of two separate subparallel seminal receptacles in Bistriopelma gen. nov. but strongly divergent in Phrixotrichus and by the different morphology of male palpal bulb (embolus projecting retrolaterally from tegulum in Bistriopelma gen. nov. against posteriorly in Phrixotrichus); furthermore by the presence of basal spine on prolateral tibial apophysis, the absence of the type IV urticating setae and paired tarsal claws denticulate. Bistriopelma gen. nov. is separated from Tmesiphantes hypogeus by the position of the urticating seta patches (middle of abdomen in Bistriopelma gen. nov. and posterior half in Tmesiphantes hypogeus), the different shape of spermathecae (long separate seminal receptacles with subapical constriction in Bistriopelma gen. nov. and short, subtriangular and widely separated in Tmesiphantes hypogeus) and also in the extension of metatarsal scopulae. Additional comments and a distribution map of all species of this genus are provided.